Controllable optical tuning and improvement in Li+, Eu3+-codoped BaSc2O4:Bi3+ based on energy transfer and charge compensation. Issue 24 (5th June 2018) - Dang, Peipei; Liang, Sisi; Li, Guogang; Wei, Yi; Cheng, Ziyong; Lian, Hongzhou; Shang, Mengmeng; Ho, Seong Jang; Lin, Jun
Abstract : Improved photoluminescence and efficient blue-to-red color-tuning of novel BaSc2 O4 :Bi 3+ phosphors were achieved by Li + /BaF2 lattice modification and Bi 3+ → Eu 3+ energy transfer. Abstract : In pursuit of highly efficient phosphors for white LED (w-LED) lighting, chemical modification of the host lattice and the design of energy transfer in a variety of cation sites have been extensively considered. In this work, a series of novel Bi 3+, Li +, Eu 3+ -doped BaSc2 O4 phosphors with blue-to-red tunable emission were synthesized by a high-temperature solid-state reaction process. Charge compensators (Li + ) and fluxes (BaF2 ) were jointly employed to improve the phase purity and luminescence properties of phosphors based on appropriate chemical modifications. The crystal structures were analyzed by XRD and the Rietveld refinement, and the photoluminescence properties and thermal stabilities of the studied phosphors were investigated in detail. BaSc2 O4 :Bi 3+ could be efficiently excited by n-UV light (250–350 nm), and exhibits a bright broad blue emission band (400–520 nm) with a peak at 440 nm. Moreover, the introduction of the Li + ion and BaF2 could efficiently enhance the emission intensity and decrease thermal quenching, which should be due to the lattice modification. Interestingly, systematic luminescence tuning from blue to red could be achieved by designing Bi 3+ → Eu 3+ energy transfer. The corresponding luminescence mechanism was discussed and proposed. In addition, Bi 3+, Li + -doped BaSc2 O4 phosphors with BaF2 demonstrate good thermal stability, with their emission intensity at 150 °C still exceeding 70% of the initial RT value. The above results indicate that the BaSc2 O4 :Bi 3+, Li + phosphor would be a potential blue phosphor for n-UV based w-LEDs devices. Moreover, the controllable emission adjustment from Bi 3+, Eu 3+ -codoped BaSc2 O4 phosphors could derive a series of novel phosphor materials for improving the light quality of w-LED sources.